A sigmoid-based adaptive inertia control strategy for grid-forming inverter to enhance frequency stability - Huang, Renzhi; Dong, Chen; Wu, Zaijun; Quan, Xiangjun; Wang, Zichen; Sun, Tiankui; Hou, Kai (Frontiers in Energy Research, 2023)
This paper proposes a sigmoid-based adaptive inertia control strategy for grid-forming (GFM) inverter to enhance frequency stability. Firstly, the frequency response characteristics under different disturbances are analyzed theoretically. Then, to solve the problem that fixed inertia leads to a contradiction between the maximum frequency deviation and the setting time, a nonlinear inertia regulator is investigated. This nonlinear inertia regulator, which is based on an improved sigmoid function, is applied to achieve real-time inertia by the frequency deviation. Moreover, the full-order small-signal model of the system containing the nonlinear inertia regulator is established and thus the stability of the proposed strategy is analyzed. The proposed control strategy is implemented without derivative action, which may suffer from high-frequency noises. Finally, the hardware-in-the-loop (HIL) results verify the remarkable performance of the proposed control strategy.